Nghiên cứu động học của phản ứng oxi hóa phenol đỏ trên xúc tác Fe-SBA-15 - Sơn và cộng sự, Lê Thanh (Vietnam Journal of Chemistry, 2014)
Large-pore hexagonal SBA-15 molecular sieves partially substituted with iron (III) have been synthesized in acidic media. The degree of iron (III) incorporation into SBA-15 can be controlled by a simple adjustment of the concentration of acidic solution. All samples have been characterized by XRD and N2 adsorption. The characterization of Fe-SBA-15 suggests that the iron atoms are highly dispersed and the obtained Fe-SBA-15 possesses highly ordered hexagonal structures. The obtained Fe-SBA-15 showed an excellent catalytic oxidation over phenol red. In the range of low temperature from 30 to 90oC, the rate data for the oxidation of phenol red reaction in excess H2O2 over Fe-SBA-15 catalyst can be fitted well to first order law. A Eley-Redeal type mechanism model were used to fit the proposed sites of [Fe*-H2O2]/SBA-15 and total oxidation of phenol red with the observer rate data. The model fitted to the experimental data generated in this study indicates that nature of heterogeneous catalytic sites being different from those of homogeneous ones cause its high catalytic performance.